Methodology of the input-output analysis - Julia Kowalewski (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2009)
In the near future consequences of the anthropogenic climate change will be more and more perceptible all over the world. But the regional distribution will differ substantially even between regions within the same country. Thus, local authorities need to adapt their regions individually to the risks resulting from the new climatic conditions. By implementing climate change in specific regional models the small scale economic impacts of climate change and the economic usefulness of adaptation measures can be evaluated. The input-output method presented in this paper delivers insight into the impact chain through which endogenous shocks affect the economy. The methodology is relatively uncomplex compared to other model types. Thus, the results are quite easy to understand and to communicate to the public. On the other hand the results underlie several restrictive assumptions. In the empirical environmental literature the input-output method is common for the assessment of economic damages after disasters. But models, which implement economic effects of adaptation measures, are very scarce.
Keywords: 330; input-output model; sectoral interdependencies; impact analysis